Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1242/jeb.082545
|View full text |Cite
|
Sign up to set email alerts
|

The impact behaviour of silk cocoons

Abstract: SUMMARYSilk cocoons, constructed by silkmoths (Lepidoptera), are protective structural composites. Some cocoons appear to have evolved towards structural and material optimisation in order to sustain impact strikes from predators and hinder parasite ingress. This study investigates the protective properties of silk cocoons with different morphologies by evaluating their impact resistance and damage tolerance. Finite element analysis was used to analyse empirical observations of the quasi-static impact response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…It is known that the in-plane tensile properties of B. mori silkworm cocoons are quasi-isotropic due to their non-woven laminate structure [19,32,33]. In this study, we found that the compressive properties of the cocoon structure were dependent on the loading direction; the load-deflection curve of cocoons loaded in the longitudinal direction was considerably higher than that of cocoons loaded in the transverse direction (Fig.…”
Section: Silkworm Cocoonsmentioning
confidence: 62%
See 4 more Smart Citations
“…It is known that the in-plane tensile properties of B. mori silkworm cocoons are quasi-isotropic due to their non-woven laminate structure [19,32,33]. In this study, we found that the compressive properties of the cocoon structure were dependent on the loading direction; the load-deflection curve of cocoons loaded in the longitudinal direction was considerably higher than that of cocoons loaded in the transverse direction (Fig.…”
Section: Silkworm Cocoonsmentioning
confidence: 62%
“…1). The crystals participate in transferring compressive loads, and also resist crack initiation and propagation at the surface (until much higher loads are reached) by acting as crack-stoppers or deflectors [18,19,34]. Indeed, we found that the crystals made the cocoon harder and transformed the failure mechanism from progressive buckling and wrinkle formation (as observed in B. mori cocoons) to crack nucleation and rapid propagation.…”
Section: Silkworm Cocoonsmentioning
confidence: 68%
See 3 more Smart Citations